DEVELOPMENT OF PDF FLIP-BASED E-MODULE FOR MATHEMATICS LEARNING: PENGEMBANGAN E-MODULE BERBASIS FLIP PDF UNTUK PEMBELAJARAN MATEMATIKA - Alimuddin Tampa; Nasrullah; Khairil Amry (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
This research of development aims to develop an e-module based on Flip PDF with valid, practical, and effective integer and fraction material. This research conducted in R&D (Research and Development) design with ADDIE’s development model which included 5 stages, those are analysis, design, development, implementation, and evaluation. Respondents of the product development trial were grade VII students of SMP Negeri 25 Bulukumba with 64 students. The research instrument was a media assessment sheet by media experts and material experts to measure the validity and then questionnaires for teacher and student responses to measure the practicality of the mathematics e-module. The results showed that the mathematics e-module fulfilled the validity and practical criteria. The product meets the criteria of validity based on the assessment by the material expert with an average score of 3.88 and the assessment by the media expert with an average score of 3.33. The product meets the practicality criteria based on student responses with an average score of response at 3.72, categorized as practical, and teacher responses with an average score of response at 3.7, categorized as very practical. Based on the data criteria above, it can be concluded that the mathematics e-module can be used in learning activities. Further research can be done by developing learning media on specific abilities.